RANK signaling in osteoclast precursors results in a more permissive epigenetic landscape and sexually divergent patterns of gene expression - Keever,Abigail L.; Collins,Kathryn M.; Clark,Rachel A.; Framstad,Amber L.; Ashley,Jason W. (PeerJ, 2023)
Background Sex is an important risk factor in the development of osteoporosis and other bone loss disorders, with women often demonstrating greater susceptibility than men. While variation in sex steroids, such as estradiol, accounts for much of the risk, there are likely additional non-endocrine factors at transcriptional and epigenetic levels that result in a higher rate of bone loss in women. Identification of these factors could improve risk assessment and therapies to preserve and improve bone health. Methods Osteoclast precursors were isolated male and female C57Bl/6 mice and cultured with either MCSF alone or MCSF and RANKL. Following the culture period RNA was isolated for RNA sequencing and DNA was isolated for tagmentation and ATAC sequencing. RNA-Seq and ATAC-seq were evaluated via pathway analysis to identify sex- and RANKL-differential transcription and chromatin accessibility. Results Osteoclasts demonstrated significant alterations in gene expression compared to macrophages with both shared and differential pathways between the sexes. Transcriptional pathways differentially regulated between male and female cells were associated with immunological functions with evidence of greater sensitivity in male macrophages and female osteoclasts. ATAC-Seq revealed a large increase in chromatin accessibility following RANKL treatment with few alterations attributable to sex. Comparison of RNA-Seq and ATAC-seq data revealed few common pathways suggesting that many of the transcriptional changes of osteoclastogenesis occur independently of chromatin remodeling.
Keywords: Osteoclasts; RANK signaling; RNA-seq; ATAC-seq; Sexual dimorphism; Macrophages